Asuhan keperawatan pada keluarga dengan anak usia remaja di Kecamatan Darussalam Aceh Besar - Ahad, Fazal; Fithria, Fithria; Atika, Syarifa (Indonesian Journal of Health Science, 2025)
Background: The abuse of narcotics, psychotropic substances, and other addictive substances, as well as smoking habits, are serious issues among Indonesian adolescents, negatively impacting their health and future potential. Objective: This case study aimed to describe nursing care for families with adolescent members in Darussalam Sub-district, Aceh Besar. Method: This study employed a case study design with family nursing care approach, including assessment, diagnosis, intervention, planning, and evaluation. Results: Two main diagnoses were identified: knowledge deficiency regarding narcotics, psychotropic substances, and other addictive substances and engagement in a risky health behavior (smoking). The nursing care plan was developed based on the five family health tasks. Interventions for the first diagnosis included education on the dangers of narcotics, psychotropic substances, and other addictive substances, health support, deep breathing relaxation training, provision of health service information, and motivation to seek healthcare services. Interventions for the second diagnosis involved health education on the risks of smoking, support for smoking cessation, and the application of Spiritual Emotional Freedom Technique (SEFT) therapy to help manage smoking urges. The evaluation results showed improvements in family knowledge, skills, and motivation in enhancing their health status through the implementation of the five family health tasks. Conclusion: The nursing care increased knowledge, skills, and motivation among the families in addressing drug abuse and smoking habits among adolescents. Recommendations: Community health center nurses are encouraged to be more proactive in organizing educational and outreach programs for adolescents to prevent drug abuse and smoking, as well as to implement SEFT interventions for those who already smoke. These efforts require the participation of parents and the community, along with the provision of counselling services for adolescents. Latar Belakang: Penyalahgunaan Napza (Narkotika, Psikotropika, dan Zat Adiktif lainnya) serta kebiasaan merokok merupakan masalah serius di kalangan remaja Indonesia yang berdampak negatif pada kesehatan dan potensi masa depan mereka. Tujuan: Studi kasus ini bertujuan untuk menggambarkan asuhan keperawatan pada keluarga dengan usia remaja di Kecamatan Darussalam, Aceh Besar. Metode: Penelitian ini menggunakan studi kasus dengan pendekatan asuhan keperawatan keluarga yang meliputi pengkajian, penetapan diagnosa, intervensi, perencanaan, dan evaluasi. Hasil: Terdapat dua diagnosis utama yang diidentifikasi adalah defisien pengetahuan; Napza dan perilaku kesehatan cenderung berisiko; merokok. Perencanaan disusun berdasarkan lima tugas kesehatan keluarga. Intervensi diagnosa pertama, meliputi edukasi tentang bahaya Napza, dukungan kesehatan, pelatihan teknik relaksasi pernapasan dalam, penyediaan informasi layanan kesehatan, dan motivasi untuk mencari layanan kesehatan. Intervensi diagnose kedua mencakup pendidikan kesehatan mengenai risiko merokok, dukungan untuk berhenti merokok, dan pengajaran terapi Spiritual Emotional Freedom Technique (SEFT) untuk mengatasi dorongan merokok. Hasil evaluasi proses menunjukkan peningkatan pengetahuan, keterampilan, dan motivasi keluarga dalam meningkatkan status kesehatan mereka melalui pelaksanaan lima tugas kesehatan keluarga. Kesimpulan: Asuhan keperawatan menunjukan adanya peningkatan pengetahuan, keterampilan, dan motivasi keluarga untuk mengatasi masalah Napza dan kebiasaan merokok pada remaja. Saran: Perawat di puskesmas diharapkan lebih aktif dalam mengadakan program edukasi dan penyuluhan untuk remaja guna mencegah pengunaan Napza dan merokok, serta menerapkan intervensi SEFT pada remaja yang sudah merokok. Upaya ini memerlukan partisipasi orang tua dan masyarakat serta penyediaan layanan konseling bagi remaja.